A next-generation microarray further reveals stage-enriched gene expression pattern in the blood fluke Schistosoma japonicum. Issue 1 (December 2017) - Cai, Pengfei; Liu, Shuai; Piao, Xianyu; Hou, Nan; You, Hong; McManus, Donald; Chen, Qijun
Abstract Background Schistosomiasis is caused by infection with blood flukes of the genusSchistosoma, and ranks, in terms of disability-adjusted life years (DALYs), as the third most important neglected tropical disease. Schistosomes have several discrete life stages involving dramatic morphological changes during their development, which require subtle gene expression modulations to complete the complex life-cycle. Results In the current study, we employed a second generation schistosome DNA chip printed with the most comprehensive probe array for studying theSchistosoma japonicum transcriptome, to explore stage-associated gene expression in different developmental phases ofS. japonicum . A total of 328, 95, 268 and 532 mRNA transcripts were enriched in cercariae, hepatic schistosomula, adult worms and eggs, respectively. In general, genes associated with transcriptional regulation, cell signalling and motor activity were readily expressed in cercariae; the expression of genes involved in neuronal activities, apoptosis and renewal was modestly upregulated in hepatic schistosomula; transcripts involved in egg production, nutrition metabolism and glycosylation were enriched in adult worms; while genes involved in cell division, microtubule-associated mobility, and host-parasite interplay were relatively highly expressed in eggs. Conclusions The study further highlights the expressional features of stage-associated genes in schistosomes with high accuracy. The results provide a better perspective of the biological characteristics among different developmental stages, which may open new avenues for identification of novel vaccine candidates and the development of novel control interventions against schistosomiasis.